Nurse's pocket guide : diagnoses, prioritized interventions, and rationales - Doenges, Marilynn E.; Moorhouse, Mary Frances;Murr, Alice C. (Philadelphia, Pennsylvania : F. A. Davis Company, 2010)
This book is designed to aid the practitioner and student nurse in identifying interventions commonly associated with specific nursing diagnoses as proposed by NANDA International (NANDA-1). These interventions are the activities are the activities needed to implement and document care provided to the individual client and can be used in varied settings from acute to community/home care.
Chapter 1: The nursing process -- Chapter 2: Application of the nursing process -- Chapter 3: Putting theory into practice: sample assessment tools, plans of care, mind mapping, and documentation -- Chapter 4: Nursing diagnoses in alphabetical order -- Chapter 5: Health conditions and client concerns with associated nursing diagnoses.
Includes bibliographical references and index.
Keywords: NURSING DIAGNOSIS -- HANDBOOKS